Coronary Artery Calcification Under Statin Therapy and Its Effect on Cardiovascular Outcomes: A Systematic Review and Meta-Analysis - Lai, Runmin; Ju, Jianqing; Lin, Qian; Xu, Hao (Frontiers in Cardiovascular Medicine, 2020)
Objective To compare Agatston scores between patients without statin therapy and those under standard and intensive statin therapy, and to systematically review the relationship between coronary artery calcification (CAC) progression under statin therapy and cardiovascular outcomes. Methods Literature search was conducted across databases. RCTs and observational studies that reported Agatston scores at baseline and follow-up from patients with and without statin therapy were included. A systematic review and meta-analysis was conducted. Results Seven studies were subjected to qualitative and quantitative analysis. Agatston scores in all groups were increased at follow-up. Meta-analysis of data from the included studies revealed an insignificantly lower CAC score at follow-up in the experimental groups. Subgroup analysis showed that statins slowed down CAC progression mildly but significantly in population with baseline CAC score above 400 in the experimental groups (P = 0.009). Despite that calcification progressors had worse cardiovascular outcome than did non-progressors, it appeared that baseline CAC score had more decisive effects on cardiovascular outcomes. CAC progression under statin therapy did not increase cardiovascular risk, though more supportive data are needed. Conclusion Statins do not reduce or enhance CAC as measured by Agatston score in asymptomatic populations at high risk for cardiovascular diseases, but seem to slow down CAC progression. Although our result was robust, it was restricted by small sample size and relatively short follow-up period. Further studies on the relationship between CAC progression under statin therapy and cardiovascular outcomes are needed.